IICA´s contribution to the agricultural sector in Trinidad and Tobago during 1987 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
50 páginas. Series IICA Miscellaneous Publication A 2/TT-88-006.